A New Case of 13q12.2q13.1 Microdeletion Syndrome Contributes to Phenotype Delineation - Mandrile, Giorgia (Case Rep Genet, 2014)
A recently described genetic disorder has been associated with 13q12.3 microdeletion spanning three genes, namely, KATNAL1, LINC00426, and HMGB1. Here, we report a new case with similar clinical features that we have followed from birth to 5 years old. The child carried a complex rearrangement with a double translocation: 46,XX,t(7;13)(p15;q14),t(11;15)(q23;q22). Array-CGH identified a de novo microdeletion at 13q12.2q13.1 spanning 3–3.4 Mb and overlapping 13q12.3 critical region. Clinical features resembling those reported in the literature confirm the existence of a distinct 13q12.3 microdeletion syndrome and provide further evidence that is useful to characterize its phenotypic expression during the 5 years of development.